Numerical modelling of a 32 m deep excavation in the suburbs of Paris - Nejjar, Khadija; Dias, Daniel; Cuira, Fahd; Chapron, Gilles; Le Bissonnais, Hervé (Engineering structures, 2022)
•Plastic clay can be modelled in drained conditions.•FEM-3D calculations are appropriate to reproduce on site recorded displacements.•SRM underestimates the props loads. As part of the Grand Paris Express project, Fort d’Issy-Vanves-Clamart (FIVC) is one of the 60 new metro stations involving a 32 m deep excavation in layered soils made of limestones and clays. The support system was subject to a comprehensive monitoring program to assess the behavior of the soil and the structure during the works [22]. It comprises wall displacements using inclinometers, bending moments using fiber optic, struts and beams loads using strain gauges and earth pressures at the soil/wall interface using pressure cells. The present paper presents the back analysis done using Finite Elements Models (FEM) in 2D and 3D and, the subgrade reaction method (SRM). The results depict a great consistency between FEM and SRM in terms of reproducing, at the same accuracy level, the wall displacements and bending moments. However, the earth pressure redistribution behind the wall and the props loads are significantly underestimated by SRM (40%) especially for deep excavations. Only FEM can reproduce the measurements since arching effect is allowed within the soil. The present back analysis provides adjustment to the input soil parameters in compliance with their variation range. The resulting set of parameters could be used for an optimization purpose in future designs of deep excavations in similar ground conditions.